An epidemiological study on herbal product self-medication practice among psychotic outpatients from Serbia: A cross-sectional study - Gordana Nikolić; Nikola M. Stojanović; Pavle J. Randjelović; Snežana Manojlović; Niko S. Radulović (Elsevier, 2018)
Utilization of herbal products (HPs) is a common practice in the traditional medicine of people from southeastern Serbia. In this study, we focused on the usage of HPs as a self-medication practice among patients diagnosed with a mental illness, by aiming to ascertain the usage prevalence, the identity of the main plant taxa utilized, their formulations and target symptoms. This was accomplished through a cross-sectional study of psychiatric outpatients, conducted in the Clinic for Mental Health Protection in Niš, and which included a questionnaire on HP utilization and a non-structured psychiatric interview. Typically, single, middle-aged males, with a secondary education degree, utilized Matricaria chamomilla and/or Melissa officinalis in a form of an infusion (tea) for relieving anxiety and psychotic symptoms. In some cases, adverse effects were noted when HPs were used in combination with prescribed psychotropic medications. Our and previous results urge a thorough evaluation of possible benefits and/or harmful interactions of HP with standard medication in the treatment of psychiatric patients.